A PID controller circuit using commercially available devices - ชัยสายัณห์, อิทธิพงศ์; เพียงพรานทอง, สมเกียรติ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2022)
In this paper, a PID controller employing current feedback operational amplifier (CFOA) is designed. The advantage of proposed circuit are independently adjustable parameters (KP, KI, KD) and commercially available used devices. Mathematical analyses like sensitivities and the effects of the non-ideal of CFOA find that the active and passive element sensitivities are equal to unity in magnitude. Simulation results using LTspice are shown that the parameters (KP, KI, KD) can be independently adjusted and the power consumption of PID controller circuit 0.4 W at ±15 V supply voltages. In addition, this PID circuit is demonstrated on a close loop system with the third order plant. The simulation results using LTspice are compared with that using MATLAB. It found that both results are consistent.